Tartrate resistant acid phosphatase (TRAP) positive cells in rheumatoid synovium may induce the destruction of articular cartilage. Issue 3 (1st March 2003) - Tsuboi, H; Matsui, Y; Hayashida, K; Yamane, S; Maeda-Tanimura, M; Nampei, A; Hashimoto, J; Suzuki, R; Yoshikawa, H; Ochi, T
Abstract : Objective: To examine the role of tartrate resistant acid phosphatase (TRAP) positive mononuclear and multinucleated cells in the destruction of articular cartilage in patients with rheumatoid arthritis (RA). Methods: The presence of TRAP positive cells in the synovial tissue of patients with RA was examined by enzyme histochemistry and immunohistochemistry. Expression of mRNAs for matrix metalloproteinases (MMPs) was assessed by the reverse transcriptase-polymerase chain reaction (RT-PCR) and northern blot analysis. Production of MMPs by mononuclear and multinucleated TRAP positive cells was examined by immunocytochemistry, enzyme linked immunosorbent assay (ELISA) of conditioned medium, and immunohistochemistry of human RA synovial tissue. In addition, a cartilage degradation assay was performed by incubation of 35 S prelabelled cartilage discs with TRAP positive cells. Results: TRAP positive mononuclear cells and multinucleated cells were found in proliferating synovial tissue adjacent to the bone-cartilage interface in patients with RA. Expression of MMP-2 (gelatinase A), MMP-9 (gelatinase B), MMP-12 (macrophage metalloelastase), and MMP-14 (MT1-MMP) mRNA was detected in TRAP positive mononuclear and multinucleated cells by both RT-PCR and northern blot analysis. Immunocytochemistry for these MMPs showed that MMP-2 and MMP-9 were produced by both TRAP positive mononuclear and multinucleated cells, whereas MMP-12 and MMP-14 were produced by TRAP positive multinucleated cells. MMP-2 and MMP-9 were detected in the conditioned medium of TRAP positive mononuclear cells. TRAP positive mononuclear cells also induced the release of 35 S from prelabelled cartilage discs. Conclusion: This study suggests that TRAP positive mononuclear and multinucleated cells located in the synovium at the cartilage-synovial interface produce MMP-2 and MMP-9, and may have an important role in articular cartilage destruction in patients with RA.